(3Ce GdYHQ aj PcQ ef eVi heQs - (3YHO GdSdGe Hf YeQ Hf eMeO GdeGQOjfj,J (B1259 (3g` s ((3YeQ Hf YHO GdSdGe Hf YeQ Hf eMeO GdeGQOjfi GdMfai s)
(3ChdgG (B:s
(3GdMeO ddg GdPi YLR GdhGO Uahf Yf hUag CeG HYO adeG cGf ai GdJhGQjN YHOI def GYJHQ aCMHHJ Cf GPcQ fHPI ef CMhGd Gdedhc hGdSdGWjf s
(3BNQgG (B:s
(3hJhLgJ GdMcheI Edi eMeO fLjH HGTG hGdi GdTGe abOe efgG heQ Ydi eGQOjf hJhLg fMh HZOGO hPdc ai LeGOi GdCNQI SfI (B1258 (3GSJQGM bde GdabjQ YeQ s
(3cJHgG GHf GdeDdas
(3cJH GdeNWhW HNW ajg edGeM GdNW GdaGQSis
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs